Cover Image, Volume 2, Issue 4. Issue 4 (12th August 2019) - Unknown
Crystallization Kinetics and Superstructure Of Poly(Butylene 2, 6‐Naphthalate): Crystallization of poly (butylene 2, 6‐naphthalate) (PBN) may follow Ostwald's rule of stages at specific cooling conditions, involving transformation of the melt into a liquid‐crystalline mesophase in a first step, followed by conversion of the latter into crystals. The cover image shows the liquid crystalline mesophase as it appears between crossed polarizers in an optical microscope, with the colors providing information about the orientation of the mesogens. In their article e10044, Qian Ding and her coworkers provide detailed information about the change of crystallization kinetics and the superstructure of PBN when partially replacing butylene by diethylene sub‐units. (DOI:10.1002/PCR210044 )